2011
DOI: 10.2147/ijn.s27538
|View full text |Cite
|
Sign up to set email alerts
|

Topical delivery of DNA oligonucleotide to induce p53 generation in the skin via thymidine dinucleotide (pTT)-encapsulated liposomal carrier

Abstract: Introduction Transcription factor p53 has a powerful tumor suppressing function that is associated with many cancers. Since the molecular weight of p53 is 53 kDa, it is difficult to transport across cell membranes. Thymidine dinucleotide (pTT) is an oligonucleotide that can activate the p53 transcription factor and trigger the signal transduction cascade. However, the negative charge and high water solubility of pTT limit its transport through cellular membranes, thereby preventing it from reachin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…The prepared liposomes were stable and delivered both the drugs at a predetermined rate which showed the effectiveness of the liposomal delivery system for the treatment of skin conditions (Kochar et al, 2020). Various studies have reported effective skin permeability using liposomal nanocarrriers (Fang et al, 2011;Amer et al, 2019;Vyas et al, 2013). Formulation with higher lipid (Guggu lipid) concentration showed good drug retention after 24 h. The formulation was stable at higher temperature for longer duration.…”
Section: Evaluation Of Hypothesismentioning
confidence: 89%
“…The prepared liposomes were stable and delivered both the drugs at a predetermined rate which showed the effectiveness of the liposomal delivery system for the treatment of skin conditions (Kochar et al, 2020). Various studies have reported effective skin permeability using liposomal nanocarrriers (Fang et al, 2011;Amer et al, 2019;Vyas et al, 2013). Formulation with higher lipid (Guggu lipid) concentration showed good drug retention after 24 h. The formulation was stable at higher temperature for longer duration.…”
Section: Evaluation Of Hypothesismentioning
confidence: 89%